Conditional Cooperation and Betrayal Aversion - Robin P. Cubitt; Simon Gaechter; Simone Quercia (Center for Economic Studies and ifo Institute (CESifo), 2015)
We investigate whether there is a link between conditional cooperation and betrayal aversion. We use a public goods game to classify subjects by type of contribution preference and by belief about the contributions of others; and we measure betrayal aversion for different categories of subject. We find that, among conditional cooperators, only those who expect others to contribute little to the public good are significantly betrayal averse, while there is no evidence of betrayal aversion for those who expect substantial contributions by others. This is consistent with their social risk taking in public goods games, as the pessimistic conditional cooperators tend to avoid contribution to avoid exploitation, whereas the optimistic ones typically contribute to the public good and thus take the social risk of being exploited.
Keywords: H41; C91; C72; D03; 330; public goods game; conditional cooperation; trust; betrayal aversion; exploitation aversion; free riding; experiments